Taxonomic review of the North American species of the accentuata and celer groups of the genus Anyphaena Sundevall, 1833 (Araneae: Anyphaenidae), with description of eight new species - García-García, Miguel Ángel; Ibarra-Núñez, Guillermo; Sánchez-García, José Antonio; Jiménez, María Luisa (Zootaxa, 2026)
Anyphaena is a diverse spider genus with 66 species distributed in North America. This is the type genus of the family Anyphaenidae and comprises five species groups (accentuata, celer, pacifica, pectorosa and porta), with the celer group having the highest species richness. Here, we conducted an extensive revision of Anyphaena specimens from several North American spider collections, as part of a comprehensive study of the accentuata and celer species groups in the region. As main results, we emended the descriptions with detailed information for male and female genitalia for two the previously proposed species of accentuata group and thirty-two previously proposed species of celer group from North America and describe eight new species from Mexico: A. brescoviti sp. nov., A. estriada sp. nov., A. mateoi sp. nov., A. martinezae sp. nov., A. monserratae sp. nov., A. platnicki sp. nov., A. reynae sp. nov. and A. sundevalli sp. nov. Furthermore, we provide new geographical records for A. subgibba O. Pickard-Cambridge, 1896, A. dixiana (Chamberlin & Woodbury, 1929) and A. arbida Platnick, 1974 from Mexico, and A. subgibba from Panama. We provide photographs of habitus and genitalia for the previous described species. We also provide updated distribution maps and an identification key for all the North American species of the celer group.